Neuropedagogical strategies for teaching foreign languages to preschool children within the framework of the "Ilk qadam" state program and digital transformation in Uzbekistan (Международный научный журнал «Инженер», 2026)
This research paper provides a comprehensive analysis of the neurophysiological foundations of foreign language acquisition in the preschool education system. Within the framework of the "Ilk Qadam" state curriculum, the effectiveness of neuropedagogical approaches is explored, specifically focusing on the relationship between brain plasticity and cognitive development. The article scientifically substantiates the role of digital technologies and interactive musical tools in the process of linguistic coding. The research findings indicate the necessity of implementing an educational model based on multisensory integration and neurobiological principles to enhance the intellectual potential of preschool children.